Knowledge Hiding by Salespeople in a B2C Context - Cordeiro Medeiros Mondego; Clarisse; Mainardes Wagner, Emerson (Wiley, 2026)
This study sought to explore the possible reasons why salespeople hide knowledge from customers in a business-to-consumer context (B2C). Based on the existing literature on knowledge hiding at the individual, organizational, and sales levels, an exploratory methodology with a qualitative approach was adopted. Interviews were conducted with 16 customers and 24 salespeople from different sectors. Based on the content analysis, a theoretical model was developed consisting of three categories that together explain the reasons for knowledge hiding by salespeople. Individual factors indicate that salespeople show intentional behavior, on a personal level, to hide knowledge requested by customers. At the organizational level, culture, leadership, and organizational climate can lead to knowledge hiding. Finally, in relational terms, knowledge hiding can occur in the interaction between salespeople and customers, a phenomenon that has not yet been identified in literature. The results provide input for improving sales practices and strategies, as well as enhancing value propositions for customers. Understanding the reasons behind knowledge hiding can contribute to better management and training of sales staff.